HUBUNGAN BILATERAL INDONESIA DAN PALESTINA, TERHADAP IMPOR KURMA KE PASOKAN PANGAN INDONESIA - Ning Ai Satyawati; Anak Agung Bagus Putu Widanta (Berajah Journal, 2026)
Food security is a crucial pillar in maintaining national stability, as the supply of certain commodities often depends on the dynamics of international relations. Through economic diplomacy, Indonesia has established strategic cooperation with Palestine, manifested through special trade policies regarding dates. This study aims to analyse the influence of import volume, international prices, and bilateral relations policies on the supply of dates in Indonesia during the observation period of 2013–2024. The methods used in this study include quantitative analysis employing the Autoregressive Distributed Lag (ARDL) approach and a structural break test to detect fundamental changes in the data. The results indicate that, simultaneously, import volume, international prices, and bilateral relations have a significant impact on the supply of dates in Indonesia. Partially, the international price variable has a positive and significant effect on supply in the short term, while bilateral relations policies through import duty exemptions have a positive but statistically insignificant effect on long-term supply stability. These findings indicate that although diplomatic policies are capable of opening market access, domestic supply stability remains highly vulnerable to global price fluctuations. Therefore, it is necessary to optimize trade policy instruments and strengthen more comprehensive bilateral cooperation to ensure the sustainability of the national food supply.